Der Text der Oberammergauer Passionsspiele 2000: Ein Produkt des christlich-jüdischen Dialoges und ein Testfall für dessen gegenwärtigen Stand - Reinbold, Wolfgang (Zeitschrift für Theologie und Kirche, 2001)
For decades, the Oberammergau Passion Play has been notorious for its anti-Jewish stance. In the year 2000, the work was revised thoroughly. Its new text is a remarkable example of the excellent progress that has been made in the recent Christian-Jewish dialogue in Germany, and also of its current limitations.